2017
DOI: 10.3390/ani7030021
|View full text |Cite
|
Sign up to set email alerts
|

Individual Ranging Behaviour Patterns in Commercial Free-Range Layers as Observed through RFID Tracking

Abstract: Simple SummaryUnderstanding of how free-range laying hens on commercial farms utilize the outdoor space provided is limited. In order to optimise use of the range, it is important to understand whether hens vary in their ranging behaviour, both between and within individual hens. In our study, we used individual tracking technology to assess how hens in two commercial free-range flocks used the range and whether they varied in their use of the range. We assessed use of three areas at increasing distance from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 25 publications
3
51
1
2
Order By: Relevance
“…Conversely, hens also spent a large proportion of their time foraging in the wintergarden, likely stimulated by the presence of litter . Indeed, hens foraged mostly in the wintergarden or in the far range, but a complementary RFID tracking study of the same study flock (referred to as Flock A) showed that hens spent half of their time outdoors in the wintergarden and less time further away in the range.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…Conversely, hens also spent a large proportion of their time foraging in the wintergarden, likely stimulated by the presence of litter . Indeed, hens foraged mostly in the wintergarden or in the far range, but a complementary RFID tracking study of the same study flock (referred to as Flock A) showed that hens spent half of their time outdoors in the wintergarden and less time further away in the range.…”
Section: Discussioncontrasting
confidence: 72%
“…If the same focal hen was randomly chosen again within the same recording, the nearest hen was used instead. Individual hens were not identified, but a complimentary study of the same flock showed that hens spent, on average, less than 20 min in each outdoor area, meaning it is unlikely the same hens were recorded in consecutive videos. The number of focal birds was also recorded, because some time points had less than five focal birds present.…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…However, each hen within a group has a different ranging behavioural pattern. To monitor the outdoor ranging behaviour of individual chickens, RFID systems have been used by attaching tags on chickens and putting antennas at pop holes, through which chickens move inside and outside (Gebhardt-Henrich et al, 2014;Campbell et al, 2017;Larsen et al, 2017). The frequency and duration of visiting the outdoor areas are then calculated by analysing data from chickens walking over the antennas.…”
Section: Tracking Movement and Feeding Behaviour Of Individualsmentioning
confidence: 99%
“…For the first problem, we can use indicators such as the reading frequency, phase value, and RSSI of the tag [14][15][16]. The phase difference and the received signal strength indication reflect the difference between the real received signal and the antenna transmitted signal [17][18][19]. As it is related to the environment, the phase value and RSSI of the tag are affected by the multipath effect in the environment [20,21].…”
Section: Related Workmentioning
confidence: 99%